2021
DOI: 10.3390/ani12010013
|View full text |Cite
|
Sign up to set email alerts
|

Low-Intensity, High-Frequency Grazing Strategy Increases Herbage Production and Beef Cattle Performance on Sorghum Pastures

Abstract: We assessed the effects of high-intensity and low-frequency (HILF) vs. low-intensity and high-frequency (LIHF) grazing on herbage production and performance of beef cattle grazing sorghum pastures. The experimental design was a complete randomized block with two treatments and four replicates (paddocks), carried out in 2014/15. The management target of 50 and 30 cm for pre- and post-grazing, respectively, a LIHF grazing management strategy oriented to maximize beef cattle herbage intake per unit time, was comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…We hypothesize that growth rate will be maintained in the exponential phase of the curve, thus promoting a higher frequency of grazing events. Studies by Savian et al (2018), Savian et al (2020), Schons et al (2021) and Portugal et al (2022) support this idea. In a long‐term study, Savian et al (2020) and Schons et al (2021) applied this concept comparing “Rotatinuous stocking” (RN – SSH pre‐grazing of 18 cm and SSH post‐grazing of 11 cm) to traditional rotational stocking (RT – SSH pre‐grazing of 25 cm and SSH post‐grazing of 5 cm) of sheep grazing Lolium multiflorum .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…We hypothesize that growth rate will be maintained in the exponential phase of the curve, thus promoting a higher frequency of grazing events. Studies by Savian et al (2018), Savian et al (2020), Schons et al (2021) and Portugal et al (2022) support this idea. In a long‐term study, Savian et al (2020) and Schons et al (2021) applied this concept comparing “Rotatinuous stocking” (RN – SSH pre‐grazing of 18 cm and SSH post‐grazing of 11 cm) to traditional rotational stocking (RT – SSH pre‐grazing of 25 cm and SSH post‐grazing of 5 cm) of sheep grazing Lolium multiflorum .…”
Section: Discussionmentioning
confidence: 85%
“…,Savian et al (2020),Schons et al (2021) andPortugal et al (2022) support this idea.In a long-term study,Savian et al (2020) andSchons et al (2021) applied this concept comparing "Rotatinuous stocking" (RN -SSH pre-grazing of 18 cm and SSH post-grazing of 11 cm) to traditional rotational stocking (RT -SSH pre-grazing of 25 cm and SSH post-grazing of 5 cm) of sheep grazing Lolium multiflorum. Greater total herbage production (RN = 8714 and RT = 6822 kg DM ha À1 ) and herbage accumulation rate (RN = 52.1 and RT = 33.2 kg DM ha À1 day À1 ) and greater individual performance of the animals (RN = 0.12 and RT = 0.05 kg animal-À1 day À1 ) were documented in the "Rotatinuous stocking" treatment, in which the animals began grazing a paddock at the SSH predicted for STIR -max and removed from the paddock when the SSH had been reduced by 40%.…”
mentioning
confidence: 73%
“…Te growth dynamics of the morphological components of Pennisetum, such as tillering, leaves, stems, and dead material, constantly increase up to 151 days [25]. For this reason, Portugal et al [33] argued that tropical pastures need more efcient handling, because they present high rates of pasture mass accumulation due to the high number of tillers, but quality could deteriorate more quickly.…”
Section: Resultsmentioning
confidence: 99%
“…Forage from pastures under RSL and RSM showed greater NDF concentration, but similar IVDOM compared to CS at average canopy height of 20 cm, although the IVDOM was less at the taller mean canopy height when managed at RSL and RSM (Table 5). The difference in IVDOM between average canopy height for pastures under RS suggests that the canopy target adopted may impact animal performance due its effect on forage nutritive value (Euclides et al, 2016; Portugal et al, 2022). It has been suggested that animal behaviour may be affected by canopy height, and it may impact animal performance (Herling et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…and Sorghum sudanense (Piper) Stapf cv. EMBRAPA BRS 802 mixture] favoured both FA and animal performance (Portugal et al, 2022).…”
mentioning
confidence: 99%